Cladistic Analysis of Lestremiinae (Diptera: Cecidomyiidae) - Carmo Neto, Antonio Marcelino do (2022)
Tiny mycophagous midges of the family Cecidomyiidae are easily overlooked by researchers as they are inconspicuous, unlike the galling species that leave showy traces of their presence in the form of entomogen galls and have been studied more consistently. Nevertheless, mycophagous species represent 25% of the species richness of this very diverse family (6,590 species in 812 known genera), and they are ubiquitous in the natural environment as part of the recycling of nutrients by their association with decaying vegetal matter and fungi. The subfamily Lestremiinae sensu Jaschhof & Jaschhof is one of the five within Cecidomyiidae that are entirely composed by mycophagous species. This subfamily is one of the most ancient clades of Cecidomyiidae, including 13 extant genera and 103 extant and three fossil species. Generic boundaries are often hampered because many morphological characters used to define Lestremiinae taxa lack comprehensive and comparative studies under modern approaches. Antennal sensilla are of great taxonomic importance, but there is no study of its ultrastructure for any mycophagous Cecidomyiidae. Likewise, there is no quantitative analysis of the many characters of traditional usage in the taxonomy of Lestremiinae that varies continuously. Among the several new taxa found and waiting to be named, there are some that did not correspond to any of the described genera as they are currently defined, thus we hypothesized the discovery of new genera. As the validity, boundaries, and interrelationships of lestremiine genera were largely unclear, this study aimed to revise Lestremiinae taxonomic and morphological diversity, test the monophyly of the subfamily, presenting a hypothesis of phylogenetic relationships among genera, placing the new neotropical taxa and erecting and describing new supraspecific taxa accordingly. Specimens studied were sampled from all over Brazil, besides specimens from collections in North America and Europe. Specimens of six genera were studied with Scanning Electron Microscopy in order to assess the ultrastucture of the sensilla of antenna and palpus. The data matrix consisted of 54 ingroup species of 12 genera, plus 21 outgroup species representing all the other subfamilies of Cecidomyiidae and the families Bibionidae, Mycetophilidae and Sciaridae. Parsimony analysis were performed in TNT 1.5, through searches with New Technologies, under extended implied weighting. The results include the revision of the genera Insulestremia and Anaretella in the Neotropics, including description of new species; fifteen subtypes of sensilla found in the head of lestremiinae species, two of them being exclusive; a matrix with 282 morphological characters, 162 quantitative, that allowed the reconstruction of a single, stable Most Parsimonious Tree under K=10, which is the first phylogeny of Lestremiinae. Eleven of the recognized lestremiine genera were recovered as monophyletic (Neolestremia was not included in the analysis). Species previously placed in Allarete were split into four genera, including three new. Conarete is considered a junior synonym of Anarete. A new neotropical taxon was corroborated as the representant of a new genus. Two fossil Lestremia species were fitted within the framework of the phylogeny, being raised as composing a new, fossil genus.